2017
DOI: 10.1111/eva.12484
|View full text |Cite
|
Sign up to set email alerts
|

Severe consequences of habitat fragmentation on genetic diversity of an endangered Australian freshwater fish: A call for assisted gene flow

Abstract: Genetic diversity underpins the ability of populations to persist and adapt to environmental changes. Substantial empirical data show that genetic diversity rapidly deteriorates in small and isolated populations due to genetic drift, leading to reduction in adaptive potential and fitness and increase in inbreeding. Assisted gene flow (e.g. via translocations) can reverse these trends, but lack of data on fitness loss and fear of impairing population “uniqueness” often prevents managers from acting. Here, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 110 publications
(210 reference statements)
5
138
0
2
Order By: Relevance
“…Estimates of natural levels and directions of gene flow can inform the design of optimal deployment of PALs through AGF or deployment of offspring from crosses between northern and more southern corals (Harrisson et al, 2016;Pavlova et al, 2017). Estimates of gene flow will also help inform how fast PALs may spread naturally following intervention, thereby providing guidance for the number and location of reefs where migrants harboring PALs can be best deployed.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of natural levels and directions of gene flow can inform the design of optimal deployment of PALs through AGF or deployment of offspring from crosses between northern and more southern corals (Harrisson et al, 2016;Pavlova et al, 2017). Estimates of gene flow will also help inform how fast PALs may spread naturally following intervention, thereby providing guidance for the number and location of reefs where migrants harboring PALs can be best deployed.…”
Section: Re Sultsmentioning
confidence: 99%
“…AGF and selective breeding may introduce genotypes that are not adapted to local environmental conditions other than temperature at the receiving location ("local is best", Rehfeldt et al, 2017) and introduce trade-offs between different traits. One concern is that the single or repeated pulse of PALs will erode or alter local adaptation among coral populations, as other loci adapted to the source reef conditions will also enter the receiving population (Drury, Manzello, et al, 2017;Drury, Schopmeyer, et al, 2017;Kenkel et al, 2013;Pavlova et al, 2017;Polato et al, 2010;Webber & Scott, 2012). Meta-analyses across highly divergent taxa including plants, animals, fungi, and protists revealed that local populations gain ~50% fitness advantage in their native environment compared to migrants (Hereford, 2009).…”
Section: Risks and Trade-offs Associated With Assisted Gene Flowmentioning
confidence: 99%
“…Several population‐level metrics are reported, including probability of extinction over the modelled time period. With translocation of suitable genotypes, Pavlova et al () found that the probability of extinction in the smallest populations could be maintained at or near zero for 100 years, a substantial improvement on a “do‐nothing” scenario.…”
Section: Setting Ecologically Realistic Targets For Fishway Effectivementioning
confidence: 99%
“…Above these scales, sample sizes are greater, but drift–migration equilibrium may take longer to occur, and stochastic processes weaken correlations. Understanding the scale dependence of IBD may be important to understanding why different studies on a specific species obtain different IBD inferences and help to inform whether an IBD study has sufficient power to identify effects of landscape features on population connectivity. Urbanization's influence on isolation and genetic diversity : We hypothesized that greater urbanization will affect metapopulation dynamics by increasing among‐population isolation and reducing within‐population genetic diversity for both species, relative to patterns in less‐urbanized areas (Frankham, ; Kenney, Allendorf, Mcdougal, & Smith, ; Pavlova et al, ). We further hypothesize that the substantive differences in life history and vagility of our focal species will contribute to different effects of the same landscape features (Moyle, ; Phillipsen et al, ).…”
Section: Introductionmentioning
confidence: 99%